2022
DOI: 10.1163/15685381-bja10093
|View full text |Cite
|
Sign up to set email alerts
|

Sex, size and eco-geographic factors affect the feeding ecology of the Iberian adder, Vipera seoanei

Abstract: Numerous dietary studies have shown that European vipers (genus Vipera) present low feeding frequency and a specialist diet, which is characterised by a marked ontogenetic shift. However, how eco-geographic factors shape species’ feeding ecology remains scarcely addressed. We investigated the feeding ecology of the Iberian adder, Vipera seoanei, examining 402 specimens distributed across its distributional range and addressing how biological, temporal and eco-geographic factors relate to the species feeding ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…For example, those snake species living in dry habitats and feeding on rodents are weakly infested by helminths (Kirillov and Kirillova 2021). Although the factors found here as predictors of helminth occurrence are not the same as those related to the consumption of major prey types in this viper species (Espasandín et al 2022), they align with the aforementioned pattern in V. seoanei. Helminths occur in vipers inhabiting lowlands, areas of high temperature and precipitation levels, and with abundance of pastures (Fig.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...supporting
confidence: 53%
See 4 more Smart Citations
“…For example, those snake species living in dry habitats and feeding on rodents are weakly infested by helminths (Kirillov and Kirillova 2021). Although the factors found here as predictors of helminth occurrence are not the same as those related to the consumption of major prey types in this viper species (Espasandín et al 2022), they align with the aforementioned pattern in V. seoanei. Helminths occur in vipers inhabiting lowlands, areas of high temperature and precipitation levels, and with abundance of pastures (Fig.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...supporting
confidence: 53%
“…In reptiles, body length correlates to age due to an undetermined growth throughout their life (Candan 2021). Indeed, assuming 325 mm as SVL at sexual maturation (Lucchini et al 2020;Espasandín et al 2022) we indicate that helminths were mostly found in adults of V. seoanei. This agrees with results from other reptile species in which body length also has a signi cant effect on the occurrence of parasites.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...mentioning
confidence: 78%
See 3 more Smart Citations